What’s the importance of portable tele-monitoring devices in patient therapeutic adherence? - Rodrigues, Orlando (2019)
Submitted by GASPAR (dinis@ubi.pt) on 2019-10-17T14:08:52Z No. of bitstreams: 1 265-2856-4-PB.pdf: 255999 bytes, checksum: b10bcea808e7beb512df3b6b3e7dd508 (MD5)